2016
DOI: 10.1111/jeb.12881
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal fluctuations in natural selection acting on the gall‐parasitic aphid Tetraneura sorini

Abstract: The measurement of the selection gradient is crucial for understanding the magnitude of selection acting directly on a trait and predicting the evolutionary trajectory of that trait. This study evaluated the selection gradient acting on the morphology of the gall-parasitic aphid Tetraneura sorini during the galling process and compared the strength among populations. Gall formers (first instars) frequently fight with conspecifics or heterospecifics for usurping incipient galls using their well-developed hind l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Several foundresses start galling on the same leaf and foundresses who failed to induce their own galls attack those who are inducing an incipient gall (Akimoto & Yamaguchi, ). Muramatsu and Akimoto () examined the body sizes of foundresses from nine populations, and in all of these, they detected significant directional selection for larger body size. Mothers who produce a larger number of bigger females could have more numerous granddaughters that survive the galling process and reproduce because of their better fighting ability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several foundresses start galling on the same leaf and foundresses who failed to induce their own galls attack those who are inducing an incipient gall (Akimoto & Yamaguchi, ). Muramatsu and Akimoto () examined the body sizes of foundresses from nine populations, and in all of these, they detected significant directional selection for larger body size. Mothers who produce a larger number of bigger females could have more numerous granddaughters that survive the galling process and reproduce because of their better fighting ability.…”
Section: Discussionmentioning
confidence: 99%
“…The T. sorini foundress is the largest in body size of the Tetraneura species, with well‐developed hind legs, and thus, it has an overwhelming advantage in aggressive interactions. Muramatsu and Akimoto () showed that where the density of other Tetraneura species (host species) is lower, T. sorini foundresses more frequently fight with conspecifics, such that foundresses are subject to stronger directional selection for larger body sizes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During fighting, larger body size is overwhelmingly advantageous (Whitham, ; Aoki & Makino, ; Akimoto & Yamaguchi, ). In Tetraneura sorini , foundresses are reportedly subject to directional selection for larger body size in all populations examined (Muramatsu & Akimoto, ). Therefore, where unrelated foundresses frequently fight, mothers can gain higher fitness returns by investing more resources in individual females, thereby producing larger foundresses.…”
Section: Discussionmentioning
confidence: 99%